PENGARUH EKSTRAK TEMPE TERHADAP MEKANISME DAN LAJU PERUBAHAN ß-KAROTEN DALAM SAUS CABE - Sirajuddin, Saifuddin; ., Masni (GIZI INDONESIA, 2009)
THE EFFECT OF TEMPE EXTRACT ON THE MECHANISM AND RATE OF CHANGES OF β-CAROTEN IN CHILI SAUCEChili sauce has the potential to be used as a vehicle for vitamin A fortification in the form of β-carotene, since it can be added to various foods. However, we need information about the resistanceof β-carotene in chili sauce during processing and storage. The objectives of this study are: toidentify the degradation patterns of β-carotene in chili sauce which contains tempe extract in variousconcentration during processing and storage in room temperature, and to identify the mathematicsmodel of β-carotene degradation. This study consists of three steps: preparing tempe extract usingtempe inoculum; preparing chili sauce; and analysis of changes of β-carotene in chili sauce duringprocessing and storage.The results of this study are: the tempe produced rendement extract of 14,18% with 3-hydroxianthranilic acid concentration of 33,5 mg/100 grams dried tempe; tempe extract was able toinhibit the changes of β-carotene in chili sauce caused by heating and storage in room temperature;β-carotene changes in chili sauce during storage in room temperature with and without tempe extractare following the null reaction order; mathematics model of β-carotene changes in chili sauce duringroom temperature storage can be used to determine β-carotene concentrations in storage timeintervals through kinetic reaction analysis.Keywords: chili sauce, tempe extract, β-carotene, fortification